Deflectometric method for surface shape reconstruction from its gradient - Miks, Antonin; Novak, Jiri (Optics express, 2012)
In this work we provide a theoretical analysis of gradient deflectometric method for 3D topography measurements of optically smooth surfaces. It is shown that the surface reconstruction problem leads to a nonlinear partial differential equation. A shape of a surface can be calculated by solution of a derived equation. An advantage of the presented method is a noncontact character and no need for a reference surface.
Keywords: Imaging, Three-Dimensional; testování materiálů; fotometrie; zobrazování trojrozměrné; Manufactured Materials; povrchové vlastnosti; Photometry; vyrobené materiály; Surface Properties; Materials Testing